RELEVANCE OF VARIETAL STRUCTURES IN WINTER WHEAT PRODUCTION IN PRESENT CONDITIONS - I. N. Kudryashov; L. A. Bespalova; D. А. Ponomarev (Зерновое хозяйство России)
Wheat is the most essential crop in Russia and in the whole world. Over a century in Kuban Area the average increase of its productivity was more than 40 kg of grain per hectare every year; the increase of genetic potential of its productivity due to breeding was 60 kg of grain per hectare every year. The combination of the maximum valuable traits and properties in one variety can result in the slower growth of productivity, which is the main purpose of the breeding process. The problem of the increase of winter wheat genetic diversity while maintaining the rate of growth through breeding can be solved through the use of varietal structures in the production. They require the development of agro-ecologic passports of each variety. For these purposes, Krasnodar RIA named after P.P. Lukiyanenko has been studying the biologic traits of the varieties since 1995. Over 21 years 137 varieties of wheat and triticale have been examined on more than 85 000 allotments. A new varietal policy, based on the system use of the varieties has been introduced in the Krasnodar Area. In 1995 about 80% of arable lands were occupied by 6 varieties; at present more than 40 genetically diverse cultivars are used and cultivated in the region. The productivity increase due to the change from mono-variety to varietal structures can be 5,2 hwt per ha with the improvement of grain quality. The use of the varieties with different duration of the vegetation expands the range of optimal terms for agro-technical works and stabilizes the productivity and quality of grain. The experiments with the passports promoted the improvement of the breeding process. They allow studying the correlation ‘genotype-environment’ and the correlation of economic-valuable traits and the features of their formation.